2021
DOI: 10.23986/afsci.103422
|View full text |Cite
|
Sign up to set email alerts
|

Timing and conditions modify the effect of structure liming on clay soil

Abstract: Two dates (early, normal) for application and incorporation of structure lime to clay soil were examined at four field sites, to test whether early liming had more favourable effects on aggregate stability. Aggregate size distribution measurements revealed a finer tilth at the early liming date (20 August) than the normal date (14 September). Aggregate stability estimated one year later, using as a proxy turbidity in leachate from 2–5 mm aggregates subjected to two simulated rainfall events, was significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
(33 reference statements)
2
2
0
Order By: Relevance
“…4b). This is in line with studies by Blomquist and Berglund (2021) demon strating the importance of timing and soil conditions at structure liming. Using eight variables, all seven trial sites that showed a significant effect of structure liming were correctly classified as suitable for structure liming.…”
Section: The Effect Of Structure Liming Can Be Predictedsupporting
confidence: 91%
“…4b). This is in line with studies by Blomquist and Berglund (2021) demon strating the importance of timing and soil conditions at structure liming. Using eight variables, all seven trial sites that showed a significant effect of structure liming were correctly classified as suitable for structure liming.…”
Section: The Effect Of Structure Liming Can Be Predictedsupporting
confidence: 91%
“…Structure lime in treatment SL proved to be slightly more effective in producing a finer tilth than the ground limestone in treatment GL, as the fraction of coarse aggregates (>5 mm) in SL was significantly lower than in the unlimed control and also than in treatment GL. These results are in line with observed effects of structure lime in previous studies under Swedish conditions (Blomquist 2021). In the present study, seedbed soils were examined in the second crop rotation, in the period 2018-2021, 5-7 years after liming.…”
Section: Discussionsupporting
confidence: 93%
“…In that study, the effect on soil aggregate stability after application of quicklime was instant (within two days) and persisted for a monitoring period of three months in three soils with medium clay content (27−40%). Blomquist and Berglund (2021) found that the timing and conditions at application of structure lime affect the outcome, with an early application time (mid-August) giving better results on soil aggregate stability one year after treatment than the normally recommended application time (mid-September). However, three years after treatment in that study there were no differences between the two application dates, and unfavourable soil moisture (too wet) and rain soon after application of the structure lime reduced the effect on soil structure (Blomquist and Berglund 2021).…”
Section: Yieldmentioning
confidence: 98%
“…In the studies by Blomquist et al (2018), Blomquist and Berglund (2021) and Blomquist et al (2022), soil aggregate stability was used as a proxy for the effect of structure liming in Swedish arable soils, particularly in the form of mitigation of P losses from clay soils. Blomquist et al (2022) identified four soil characteristics that determine the effect of structure liming on soil aggregate stability, namely clay content, initial soil pH, soil organic matter (SOM) content and soil mineral index (SmV).…”
Section: Yieldmentioning
confidence: 99%